2019
DOI: 10.14202/vetworld.2019.959-964
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the cytochrome c oxidase subunit 1 gene of Sarcoptes scabiei isolated from goats and rabbits in East Java, Indonesia

Abstract: Aim: This study aimed to sequence the Cytochrome c oxidase (COX-1) gene sequence from mitochondrial DNA of Sarcoptes scabiei isolated from Lamongan goats and Mojokerto rabbits, align it with DNA isolated from Zi'gong rabbit (GenBank accession No. EU256389.1), and produce a phylogenetic analysis of S. scabiei COX-1 gene. Materials and Methods: S. scabiei mites were obtained from goats and rabbits, and DNA was extracted using QIAamp DNA Mini Kit. The forward and reverse primer sequences were designed based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Interestingly, it is mentioned that the mange of camels can predominately be identified based on clinical signs (21). Therefore, these observations are consistent with the clinical signs of mange caused by S. scabies, where they agreed with other previous studies (21)(22)(23)(24). The molecular diagnosis (cPCR) based on COX1 shows that 29.41% of the examined camels were infested with S. scabiei.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, it is mentioned that the mange of camels can predominately be identified based on clinical signs (21). Therefore, these observations are consistent with the clinical signs of mange caused by S. scabies, where they agreed with other previous studies (21)(22)(23)(24). The molecular diagnosis (cPCR) based on COX1 shows that 29.41% of the examined camels were infested with S. scabiei.…”
Section: Discussionsupporting
confidence: 89%
“…Research by Lastuti et al [21] demonstrated that the partial CDS of mitochondrial COX-1 gene of S. scabiei from Lamongan goats was very similar to Mojokerto rabbits, with a homology identity of 99%. That previous study confirmed that out of 290 bp in Lamongan scabies-infected goats, there was one base pair different.…”
Section: Resultsmentioning
confidence: 99%
“…The ITS2 region and cox 1 gene are widely used in the molecular diagnosis of sarcoptic mange, and ITS2 sequencing is more suitable for phylogenetic studies of astigmatid mites than the characterization of different species based on geographical distribution (Alasaad et al, 2009;Oleaga et al, 2012). However, the cox 1 gene is also suitable for the phylogenetic analysis of S. scabiei (Gomez-Puerta et al, 2022;Lastuti et al, 2019;Peltier et al, 2017b). S. scabiei is distributed among three genetically distinct clades; human-origin S. scabiei from Panama and Australia comprise 2 distinct clades, respectively, and rabbit-originS.…”
Section: Discussionmentioning
confidence: 99%